Answer:
The solution
![Y (s) = 9( -1 +3 t + e^{-3 t} ) + 7 e ^{-3 t}](https://tex.z-dn.net/?f=Y%20%28s%29%20%3D%209%28%20-1%20%2B3%20t%20%2B%20e%5E%7B-3%20t%7D%20%29%20%2B%207%20e%20%5E%7B-3%20t%7D)
Step-by-step explanation:
<u><em>Explanation</em></u>:-
Consider the initial value problem y′+3 y=9 t,y(0)=7
<em>Step(i)</em>:-
Given differential problem
y′+3 y=9 t
<em>Take the Laplace transform of both sides of the differential equation</em>
L( y′+3 y) = L(9 t)
<em>Using Formula Transform of derivatives</em>
<em> L(y¹(t)) = s y⁻(s)-y(0)</em>
<em> By using Laplace transform formula</em>
<em> </em>
<em> </em>
<em>Step(ii):-</em>
Given
L( y′(t)) + 3 L (y(t)) = 9 L( t)
![s y^{-} (s) - y(0) + 3y^{-}(s) = \frac{9}{s^{2} }](https://tex.z-dn.net/?f=s%20y%5E%7B-%7D%20%28s%29%20-%20y%280%29%20%2B%20%203y%5E%7B-%7D%28s%29%20%3D%20%5Cfrac%7B9%7D%7Bs%5E%7B2%7D%20%7D)
![s y^{-} (s) - 7 + 3y^{-}(s) = \frac{9}{s^{2} }](https://tex.z-dn.net/?f=s%20y%5E%7B-%7D%20%28s%29%20-%207%20%2B%20%203y%5E%7B-%7D%28s%29%20%3D%20%5Cfrac%7B9%7D%7Bs%5E%7B2%7D%20%7D)
Taking common y⁻(s) and simplification, we get
![( s + 3)y^{-}(s) = \frac{9}{s^{2} }+7](https://tex.z-dn.net/?f=%28%20s%20%2B%20%203%29y%5E%7B-%7D%28s%29%20%3D%20%5Cfrac%7B9%7D%7Bs%5E%7B2%7D%20%7D%2B7)
![y^{-}(s) = \frac{9}{s^{2} (s+3}+\frac{7}{s+3}](https://tex.z-dn.net/?f=y%5E%7B-%7D%28s%29%20%3D%20%5Cfrac%7B9%7D%7Bs%5E%7B2%7D%20%28s%2B3%7D%2B%5Cfrac%7B7%7D%7Bs%2B3%7D)
<em>Step(iii</em>):-
<em>By using partial fractions , we get</em>
![\frac{9}{s^{2} (s+3} = \frac{A}{s} + \frac{B}{s^{2} } + \frac{C}{s+3}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7Bs%5E%7B2%7D%20%28s%2B3%7D%20%3D%20%5Cfrac%7BA%7D%7Bs%7D%20%2B%20%5Cfrac%7BB%7D%7Bs%5E%7B2%7D%20%7D%20%2B%20%5Cfrac%7BC%7D%7Bs%2B3%7D)
![\frac{9}{s^{2} (s+3} = \frac{As(s+3)+B(s+3)+Cs^{2} }{s^{2} (s+3)}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7Bs%5E%7B2%7D%20%28s%2B3%7D%20%3D%20%20%5Cfrac%7BAs%28s%2B3%29%2BB%28s%2B3%29%2BCs%5E%7B2%7D%20%7D%7Bs%5E%7B2%7D%20%28s%2B3%29%7D)
On simplification we get
9 = A s(s+3) +B(s+3) +C(s²) ...(i)
Put s =0 in equation(i)
9 = B(0+3)
<em> B = 9/3 = 3</em>
Put s = -3 in equation(i)
9 = C(-3)²
<em>C = 1</em>
Given Equation 9 = A s(s+3) +B(s+3) +C(s²) ...(i)
Comparing 'S²' coefficient on both sides, we get
9 = A s²+3 A s +B(s)+3 B +C(s²)
<em> 0 = A + C</em>
<em>put C=1 , becomes A = -1</em>
![\frac{9}{s^{2} (s+3} = \frac{-1}{s} + \frac{3}{s^{2} } + \frac{1}{s+3}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7Bs%5E%7B2%7D%20%28s%2B3%7D%20%3D%20%5Cfrac%7B-1%7D%7Bs%7D%20%2B%20%5Cfrac%7B3%7D%7Bs%5E%7B2%7D%20%7D%20%2B%20%5Cfrac%7B1%7D%7Bs%2B3%7D)
<u><em>Step(iv):-</em></u>
![y^{-}(s) = \frac{9}{s^{2} (s+3}+\frac{7}{s+3}](https://tex.z-dn.net/?f=y%5E%7B-%7D%28s%29%20%3D%20%5Cfrac%7B9%7D%7Bs%5E%7B2%7D%20%28s%2B3%7D%2B%5Cfrac%7B7%7D%7Bs%2B3%7D)
![y^{-}(s) =9( \frac{-1}{s} + \frac{3}{s^{2} } + \frac{1}{s+3}) + \frac{7}{s+3}](https://tex.z-dn.net/?f=y%5E%7B-%7D%28s%29%20%20%3D9%28%20%5Cfrac%7B-1%7D%7Bs%7D%20%2B%20%5Cfrac%7B3%7D%7Bs%5E%7B2%7D%20%7D%20%2B%20%5Cfrac%7B1%7D%7Bs%2B3%7D%29%20%2B%20%5Cfrac%7B7%7D%7Bs%2B3%7D)
Applying inverse Laplace transform on both sides
![L^{-1} (y^{-}(s) ) =L^{-1} (9( \frac{-1}{s}) + L^{-1} (\frac{3}{s^{2} }) + L^{-1} (\frac{1}{s+3}) )+ L^{-1} (\frac{7}{s+3})](https://tex.z-dn.net/?f=L%5E%7B-1%7D%20%28y%5E%7B-%7D%28s%29%20%29%20%3DL%5E%7B-1%7D%20%289%28%20%5Cfrac%7B-1%7D%7Bs%7D%29%20%2B%20L%5E%7B-1%7D%20%28%5Cfrac%7B3%7D%7Bs%5E%7B2%7D%20%7D%29%20%2B%20L%5E%7B-1%7D%20%28%5Cfrac%7B1%7D%7Bs%2B3%7D%29%20%29%2B%20L%5E%7B-1%7D%20%28%5Cfrac%7B7%7D%7Bs%2B3%7D%29)
<em>By using inverse Laplace transform</em>
<em></em>
<em></em>
![L^{-1} (\frac{1}{s^{2} } ) = \frac{t}{1!}](https://tex.z-dn.net/?f=L%5E%7B-1%7D%20%28%5Cfrac%7B1%7D%7Bs%5E%7B2%7D%20%7D%20%29%20%3D%20%5Cfrac%7Bt%7D%7B1%21%7D)
![L^{-1} (\frac{1}{s+a} ) =e^{-at}](https://tex.z-dn.net/?f=L%5E%7B-1%7D%20%28%5Cfrac%7B1%7D%7Bs%2Ba%7D%20%29%20%3De%5E%7B-at%7D)
<u><em>Final answer</em></u>:-
<em>Now the solution , we get</em>
![Y (s) = 9( -1 +3 t + e^{-3 t} ) + 7 e ^{-3t}](https://tex.z-dn.net/?f=Y%20%28s%29%20%3D%209%28%20-1%20%2B3%20t%20%2B%20e%5E%7B-3%20t%7D%20%29%20%2B%207%20e%20%5E%7B-3t%7D)